Faktor-Faktor yang Mempengaruhi Perilaku Pekerja Bangunan dalam Menghindari Kecelakaan di Area Ketinggian Bangunan di PT Wijaya Kusuma Contrctors (WKC) Proyek Grand Clasic Hotel Cikarang 2017 - Amoston Telaumbanua; Agustina Agustina (STIKes Persada Husada Indonesia, 2017)
Work accident is an unwanted and unexpected event that can cause loss of life and property. The purpose of this study is to determine the factors that influence the behavior of construction workers in avoiding the occurrence of accidents in elevation areas in PT Wijaya Kusuma Contrctors (WKC) Grand Clasic Project Hotel Cikarang 2017. Type of research is quantitative research, with research subjects are factors which affect the behavior of construction workers in avoiding the occurrence of accidents in altitude areas in PT Wijaya Kusuma Contrctors (WKC) Grand Clasic Project Hotel Cikarang 2017. This study was conducted in June-June 2017. Number of respondents as much as 70 respondents The method used in sampling is Questionnaire, The results showed based on the results of this study the authors suggest to the company to pay more attention to factors, this is to minimize the occurrence of work accidents in the height of buildings in PT Wijaya Kusuma Contractors (WKC).